Membina integrasi antara elemen teras TQM dengan orientasi pasaran dan hubungannya dengan prestasi firma - Mohd. Ashari Idris,; Aliah Hanim M. Salleh, (Penerbit Universiti Kebangsaan Malaysia, 2002)
Past research portrayed quality orientation and market orientation as a functional discipline treated as separate orientations of the firm without any clear linkages. No relationship was apparent, eventhough these two orientations actually share a common goal, which is to generate high customer value for the firm. Past research also did not link these two orientations in a specific and detailed manner. This article therein discusses an integration of these two concepts from a theoretical perspective, and suggests an empirical framework for future studies. This framework merges the core elements of quality orientation and market orientation into an integrated model that clarifies how these elements can be mobilised to generate the firm’s competitive advantage. “Core elements of quality orientation” are proposed to be measured by four constructs comprising process optimisation and product reliability to capture the ‘operations focus’ dimension, and design optimisation and market advantage to capture the ‘external focus’ dimension. “Core elements of market orientation” will comprise five constructs, namely customer orientation, competitor orientation, technology orientation and innovation orientation, as well as organisational co-ordination. This model is also designed to frame the analysis and explain what, how and why the elements of TQM and market orientation can help to predict the firm’s performance. A set of eight propositions is also given to guide future research